Digital Money Across Borders : Macro-Financial Implications. (Policy Papers; Policy Paper ;, 2020)
Rapid ongoing progress with digital technologies has increased the prospects for adoption of new forms of digital money for both domestic and international transactions. These include central bank digital currencies (CBDCs) and the so-called global stable coins (GSCs) proposed by large technological companies or platforms. This paper explores the complex interactions between the incentives to adopt and use CBDCs and GSCs across borders and discusses the potential macro-financial effects.